IMPLEMENTASI DARI TECHNOLOGY ACCEPTANCE MODEL (TAM) DALAM MENGEVALUASI APLIKASI DESA DIGITAL - Raditya Andy Darmawan Surya (2020)
The sustainability of Industry 4.0 has now entered into the tourism sector or Tourism 4.0. Where tourism in Indonesia is a potential thing but still not as expected. Previous research shows that the applied model has not yielded optimal results in predicting platform use, so one of the steps to further study the Desa Digital mobile application research is done with the variables used in this study: Perceived Ease of Use, Perceived Usefulness, Attitude Toward Use, Intention to Use, and Actual System Usage. The aim of this research is to know the technology acceptance variable using the Technology Acceptance Model (TAM) and evaluate it. The method used in this research is to use the Partial Least Square (PLS) method. The results showed that: (1) variables influencing the acceptance of the Technology Acceptance Model, namely: Perceived Ease of Use, Perceived Usefulness, Attitude Toward Use, Intention to Use and Actual System Usage, (2) constructs that affect the model namely Perceived Ease of Use Use and Perceived Usefulness for Attitude Toward Use, Attitude Toward Use for Intention to Use and Intention to Use for Actual System Usage.